Financial protectionism: The first tests - Andrew K. Rose; Tomasz Wieladek (Bank of England, External Monetary Policy Committee Unit, 2011)
We provide the first empirical tests for financial protectionism, defined as a nationalistic change in bank's lending behaviour, as the result of public intervention, which leads domestic banks either to lend less or at higher interest rates to foreigners. We use a bank-level panel data set spanning all British and foreign banks providing loans within the United Kingdom between 1997 Q3 and 2010 Q1. During this time, a number of banks were nationalised, privatised, given unusual access to loan or credit guarantees, or reseived capital injections. We use standard empirical panel-data techniques to study effective short-term interest rates, though our data set here ist much smaller. We examine the loan mix for both British and foreign banks, both before and after unusual public interventions such as nationalisations and public capital injections. We find strong evidence of financial protectionism. After nationalisations, foreign banks reduced the fraction of loans going to the United Kingdom by about 11 percentage points and increased their effective interest rates by about 70 basis boints. By way of contrast, nationalised British banks did not significantly change either their loan mix or effective interest rates. Succinctly, foreign nationalised banks seem to have engaged in financial protectionism, while British nationalised banks have not.
Keywords: F36; G21; 330; bank; nationalisation; privatisation; crisis; loan; domestic; foreign; empirical; panel; Finanzmarkt; Bankgeschäft; Kreditgeschäft; Kapitalverkehrspolitik; Protektionismus; Zins; Großbritannien